Estratégias de internacionalização de organizações não governamentais sem fins lucrativos: um estudo multi-método - Ruiz, Fernando Martinson (2012)
There are over 50,000 international non-governmental organizations (INGOs) around the planet. Those entities are very important for a better awareness of society, they monitor corporations and government agencies, they help on the creation of intergovernmental organizations and so on. However, despite the fact that internationalization of companies and management of the third sector organizations have both been studied for several decades, there are few academic studies (especially with the management lens) that have explored the intersection of these two research fields: the internationalization of NGOs. Therefore, the main purpose of this work is to study the following research question: why do the NGOs go abroad and how are the internationalization strategies defined? After the literature review and some exploratory interviews, I conducted field research using the case study method (four cases were studied) and a survey (with 367 respondents). The main findings of the study were the perception that, for an NGO, there are more benefits than costs when going abroad, the decision process seems to be quite rational and ‘economic’ motivations are among the most important ones when going international, choosing a partner in this process and choosing the destination countries. The case studies also revealed the strong influence of the social entrepreneur on the internationalization of NGOs. It was identified a strong ‘emergent’ character in the process of going abroad, as opposed to a planned internationalization strategy. However, it was found that the higher the maturity of the international NGOs, the more is the process of geographic expansion planned. Regarding the networks of the NGOs, it was found that relationships have strong influences on the internationalization movement. The insights gathered on the survey not only confirmed the impressions we had with the cases, but also pointed out some interesting clues. The main perceived motivations to internationalize an NGO were raising funds abroad, bring best practices and meet needs abroad. Lack of knowledge of legal forms on operating abroad has been identified as the most important barrier. We also listed the main used criteria on choosing destinations abroad and the main motivators for the use of networks in the process. I have suggested several topics for future research that I believe can add some ‘bricks’ in the construction of knowledge on this field.